To Be the Best - Bradford, Barbara Taylor, 1933- (London Grafton Books, 1989)
Paula McGill O'Neill learned the lessons of success from the master - merchant princess Emma Harte, her grandmother, her teacher, her idol. Left to Paula, the legacy of Emma's international empire still thrives as the strong-willed heiress wields control with hard-earned compassion - and well-earned suspicion of every secret threat. Blessed granchild, super-wife, and loving mother, Paula has one desire - to keep her grandmother's visionary dream alive, and through sacrifice and ambition carve out an empire of her own. But every move has been shadowed by two families whose fortunes are interwined with hers - and by an unscrupulous blood enemy moving in for the kill...
Keywords: Businesswomen -- United States -- Fiction